Association of parameters of nocturnal hypoxemia with diabetic microvascular complications: A cross-sectional study. (December 2020) - Xue, Pei; Covassin, Naima; Ran, Xingwu; Zhou, Junying; Zhang, Xiaohan; Yan, Donge; Li, Xiao; Gao, Yun; Tang, Xiangdong
Abstract: Aims: To examine the association between obstructive sleep apnea (OSA)-related nocturnal hypoxemia parameters and diabetic microvascular complications in patients with type 2 diabetes mellitus (T2DM). Methods: A total of 463 Chinese patients with T2DM underwent overnight polysomnography, followed by diagnosis of diabetic microvascular complications including diabetic peripheral neuropathy (DPN), diabetic retinopathy (DR) and diabetic nephropathy (DN). Parameters of nocturnal hypoxemia, including apnea-hypopnea index (AHI), oxygen desaturation index (ODI), time spent with SpO2  < 90% (T90%) or <85% (T85%), mean SpO2 and lowest SpO2, were recorded. Results: AHI was independently associated with higher odds of DPN (OR 1.19; 95% CI, 1.05–1.36; P = 0.008) after adjustment for possible confounders. Moreover, patients with severe OSA (AHI ≥ 30 events/h) had higher likelihood of having DPN than those with mild OSA (OR 2.36; 95% CI, 1.31–4.25; P = 0.004). When combining DPN, DR and DN into an overall diabetic microvascular complication index, AHI was also independently associated with higher odds of having any diabetic microvascular complication (OR 1.21; 95% CI, 1.06–1.38; P = 0.006). Conclusions: The AHI may be the OSA-related index that most strongly reflects the association of OSA and diabetic microvascular complications, compared with other OSA-related hypoxemia parameters.